"Patient Characteristics Associated with Comfort Care among Trauma Patients at a Level I Trauma Center". Issue 11 (November 2018) - Geary, Sean P.; Brown, Maria R.; Decker, Christopher; Angotti, Lisa M.; Ata, Ashar; Rosati, Carl
Trauma patients admitted to the intensive care unit are a unique population with high mortality. This study aims to identify characteristics predicting the likelihood of progressing to palliative management often referred to as comfort care measures, thus enabling the trauma team to broach end-of-life decisions earlier in these patients' care. This is a retrospective analysis of the prospectively collected New York State Trauma Registry database for a single Level I trauma center for patients admitted from 2008 to 2015. During this time, a total of 13, 662 patients were admitted to the trauma service and there were 827 deaths, resulting in a crude annual mortality rate of approximately 6 per cent. Approximately one-half of the total mortalities, 404 of 827 (48.9%), were ultimately designated as comfort care. Univariate analysis identified the following risk factors for comfort care designation: advanced age, multiple comorbidities, blunt trauma mechanism, traumatic brain injury, and admission location. Multivariate analysis confirmed advanced age and traumatic brain injury. Subgroup analysis also identified advanced directives, pre-existing dementia, and bleeding disorders as significant associations with comfort care designation. The identification of factors predicting comfort care will result in improved care planning and resource utilization.